IMPLEMENTASI SISTEM PENDAFTARAN SISWA BARU BERBASIS WEB MENGGUNAKAN ALGORITMA SAW DI SANGGAR KEGIATAN BELAJAR UJUNG PANDANG - Sarumpaet, Calvin Bonar; Fajri, Hidayatul; Baharuddin, Suardi Hi (P3M STMIK Profesional Makassar, 2025)
The new student registration process at Sanggar Kegiatan Belajar (SKB) Ujung Pandang was previously conducted manually, resulting in several issues such as data processing delays, file accumulation, and lack of transparency in selection. This study aims to develop a web-based registration information system integrated with the Simple Additive Weighting (SAW) algorithm to enhance the efficiency and objectivity of the selection process. The system was developed using the Waterfall model and implemented using PHP and MySQL-based web technology. The implementation results show that the system can automate registration and selection in real-time. The SAW algorithm effectively produces objective participant rankings based on criteria such as exam scores, age, and domicile. Evaluation indicates that the system improves selection speed, result accuracy, and facilitates data management for users. It can be concluded that this system provides significant benefits for both SKB administrators and applicants and is relevant in supporting the digital transformation of non-formal education.